Integrating Oil Palm and Cattle Farming in South Kalimantan: Opportunities and Challenges: Livestock Distribution, Development Model and Strategy of Oil Palm-Cattle Integration Referring to Livestock Base Area in Kotabaru District in Supporting The New Capital City of Indonesia (IKN) - Biyatmoko, Danang; Susanti, Hilda; Rostini, Tintin (TROPICAL WETLAND JOURNAL, 2024)
This study examines the integration of oil palm and cattle farming in South Kalimantan, Indonesia, to support meat production for the new capital city. Kotabaru, a district with abundant oil palm plantations, faces a challenge in meeting the increasing demand for beef. This research analyzes the distribution of superior livestock, develops an oil palm-cattle integration model, and formulates development strategies. The study uses location quotient (LQ), localization index (LI), and specialization index (SI) analysis, field observations, interviews with farmers and stakeholders, and SWOT analysis. Conducted in four sub-districts of Kotabaru over eight months, the research identifies superior cattle base areas and proposes three development models: intensive, semi-intensive, and extensive. The SWOT analysis generates short-term and medium-term strategies for developing oil palm-cattle integration.